Neurologic complications in kidney transplant recipients - Piotrowski, Piotr C.; Lutkowska, Anna; Tsibulski, Alexander; Karczewski, Marek; Jagodziński, Paweł P. (Folia Neuropathologica, 2017)
Transplantology experiences continuous growth and kidney transplantation is the most frequently transplanted solid organ. Metabolic, cardiovascular, infectious or kidney function-related aspects are widely recognised and are of key interest for transplant doctors. Neurological complications seen in these patients, although known, are less covered in the literature. According to some reports, neurologic symptoms are experienced by almost 9 per 10 transplant recipients. The intensity, severity and type of abnormalities may vary, and most frequently the complications seem to be associated with a direct or indirect effect of immunosuppressive medications, including their direct effect on cells, on blood vessels, and susceptibility to infections. Increasing age of transplant recipients and relaxation of transplantation eligibility criteria enriches the population with patients already compromised, with a higher present risk of stroke, neuropathy, malignancy etc. Research on and introduction to clinical practice of new agents like belatacept, proteasome inhibitors, or modified release formulations of tacrolimus, changes the picture and type of abnormalities within the nervous or neuromuscular system but does not eliminate them. Thus, it seems justified to remind the society of the whole array of neurologic complications they can see in their practice despite advances in the field.